2003
DOI: 10.1103/physrevb.68.085326
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and intermixing in thin Ge layers on Si(001)

Abstract: In this work the Monte Carlo method with an empirical potential model for atomic interactions is applied to study reconstruction and intermixing at a Ge-covered Si͑001͒ surface. We investigate the structure and energetics of the 2ϫn reconstruction which serves as a strain-relief mechanism. The optimal value of n is found to be strongly dependent on the thickness of the Ge overlayer. Si-Ge intermixing is studied using a direct simulation method which includes entropic effects. Ge occupation probabilities in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…As such, the M ϫ N patch structure is described as an M ϫ 4 layer atop a 4 ϫ N layer, for which the upper layer does not fill in the preceding layer DVLs. Moreover, recent work 24,25 indicates that nontrivial intermixing is expected to occur across the Ge-Si interface.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the M ϫ N patch structure is described as an M ϫ 4 layer atop a 4 ϫ N layer, for which the upper layer does not fill in the preceding layer DVLs. Moreover, recent work 24,25 indicates that nontrivial intermixing is expected to occur across the Ge-Si interface.…”
Section: Introductionmentioning
confidence: 99%
“…For silicon, more than 16 empirical potentials have been proposed. 25 However, we chose SW potential for the following reasons: This potential predicts a melting temperature of silicon close to the experimental value 23 and it has been shown that SW potential describes liquid Si surface 26 and crystalline Si͑100͒ surface farely well 25,27 and that it also exhibits ͑111͒ faceting on Si͑100͒-melt interface, as observed experimentally. 4,5 Thus, the results we obtained based on SW potential are expected to be fairly accurate.…”
mentioning
confidence: 99%
“…Дальнейшее же повышение температуры (при нагреве через те-плопроводящие пути или от молекулярного пучка) приводит к высвобождению в пленке энергии на-пряжений (релаксации накопленных напряжений) в виде теплоты, что приводит к перемешиванию плен-ки с подложкой [28]. Кроме того, непрерывно, по мере зарождения и роста пленки, происходит высвобож-дение теплоты при объединении атомов в кластеры.…”
Section: рис 2 теоретические представления о механизме перемешиванияunclassified